Ameliorative impact of taurine on oxidative damage induced by Ipomoea carnea toxicity in wistar male rats through modulation of oxidative stress markers, apoptotic and Nrf2 pathway - Asmaa R. Abou El-khair (Elsevier, 2021)
Objectives: The adverse deleterious influences of Ipomoea carnea on brain tissue and Taurine's relative ability to prevent this neurotoxicity have been examined. Methods: We utilized sixty Wistar male rats weighing 1752 g. The rats were allotted into 4 groups of fifteen each: The control group got saline i.p. daily for eight weeks; the Ipomoea carnea extract (ICE) group received ICE (15 mg/kg b.w./day) orally for eight weeks. Taurine-treated rats, in which rats were administered Taurine (200 mg·kg−1, i.p./Day) for 2 months. Taurine + ICE group in which rats were supplemented with (200 mg·kg−1, i.p. Taurine + ICE 15 mg/kg b.w./day orally) for 2 months. Result: The findings indicated that Ipomoea persuaded an increase in lipid peroxidation markers as well as a disruption in antioxidant homeostasis, along with brain and serum cholinesterase (AChE) elevated levels, tumor necrosis factor (TNF), total creatine phosphokinase (CPK), creatine phosphokinase isoenzymes BB (CPK-BB), and lactate dehydrogenase (LDH). A considerable drop (P < 0.05) in the brain superoxide dismutase (SOD), catalase (CAT), and GSH in Ipomoea carnea. SOD, CAT, and GSH levels were enhanced in the Taurine co-treated group but did not achieve control levels. Ipomoea Furthermore, Induced apoptosis in brain tissue by Ipomoea carnea reflected in pro-apoptotic Bax, P53, and caspase 3 overexpression., while taurine upregulated the anti-apoptotic Bcl2 in addition to Histopathologic, electron microscope, and immunohistological brain examination finding support our finding concerning the protective role of taurine. Conclusion: Our study proved the protective role of taurine as a supplement could recover Ipomoea carnea -induced oxidative changes and brain damage.